Clinical effect of digital 3D printed maxillary protraction combined with alternate rapid maxillary expansion and constriction in the treatment of patients with skeletal Class Ⅲ malocclusion during mixed dentition - LI Gen, WANG Hua, GU Yan (Kouqiang yixue)
Objective To evaluate the skeletal effect, dental effect, soft tissue and airway changes of a digital 3D printed maxillary protraction combined with alternate maxillary rapid expansion and constriction in the treatment of skeletal Class Ⅲ patients during mixed dentition. Methods Twenty-two mixed dentition patients(mean age of (11.33±0.88) years, 9 males and 13 females) of skeletal Class Ⅲ malocclusion with maxillary hypoplasia were collected from 2018 to 2023. Treatment was performed using a digital 3D printed protraction device combined with maxillary rapid expansion and constriction. Cone-beam CT were obtained before and after treatment to assess the orthopedic treatment of hard tissue, dentition, soft tissue and airway in three dimensional direction. Results After treatment, hard tissue measurements of SNA, ANB, Wits, Co-A, and Co-Gn distance increased significantly with a statistical difference, whereas there were no statistically significant changes in SNB, FMA, Occ plane to FH and Y-axis angle. There was a statistically significant increase in U1-SN, whereas there was no significant change in U1-NA. Soft tissue measurements of upper lip distance from the E line improved with a statistically significant difference while no significant changes in nasolabial angle were detected. The volume of the posterior palatal region of the upper airway increased significantly. Conclusion The digital 3D printed maxillary protraction combined with alternate rapid maxillary expansion and constriction promotes maxillary development, inhibits mandibular development, essentially maintains vertical dimension and improves skeletal Class Ⅲ patients’ deformity and profile. The volume of the posterior palatal region of the upper airway is also significantly improved.